The content of Ayatollah Sistani’s charismatic authority: the affective bond (Antropolítica - Revista Contemporânea de Antropologia, 2024)
Historically, Ayatollah Sistani’s calls to action have mobilised hundreds of thousands and even millions of his followers into different forms of political mobilisation in the post-2003 Iraqi context (e.g. voting, demonstrations, and armed jihad). A fundamental reason for this is his charismatic authority. Pre-existing literature on Sistani’s charisma has salient shortcomings in providing a conceptually coherent framework to capture how the Ayatollah inspires Weberian ‘absolute trust’ in his religio-political leadership. The present research seeks to compensate for this by offering an alternative approach to understanding Sistani’s charisma, which is informed by 40 semi-structured interviews conducted in 2022 with his followers and other seminary and academic personalities in Iraq. The content of his charismatic authority is referred to as the ‘affective bond’, which is a cognitive-emotional connection between the followers and Sistani premised on the former’s recognition of him as a symbol of legitimacy, hope, and authenticity. These perceptions confirm the ‘absolute trust’ that followers have in Sistani, which becomes the cognitive basis of their emotional willingness to answer his calls to action. In undertaking the mission of this paper, the intimate interplay between narratives, history, culture, rituals, practices, history, storytelling, and the perceptions that produce Sistani’s charismatic authority, will come to light.